2020
DOI: 10.18280/acsm.440202
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Aging of a Concrete Reinforced by Alkali Resistant Glass Fiber in the Wet Environment

Abstract: The Glass fiber reinforced concrete (GFRC) is a composite material; it is regarded as a suitable material for concrete structures. The GFRC is reinforced with alkali resistant (AR) glass fibers, this type of glass fibers understands from 15 to 20% of the zirconium mass; this addition improves considerably the durability of glass in the alkaline environments, but does not solve entirely the problems of its degradation. Generally, the rate of aging of the composite cement-glass depends on type of glass fiber use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, it was reported that severe reductions in compressive strength and ductility may occur in GFRC with ageing [4,5], which has become a common concern for the service life of engineering members made of GFRC. e intrinsic microstructural reasons corresponding to this degradation are normally associated with chemical corrosion of fibre by the alkalinity in pore solution [6] and severe CH densification between and around fibres that results in loss of flexibility [7]. At the same time, in the global background of low carbon emission, cement industry is faced with great challenge as it contributed about 6% to total global anthropogenic CO 2 emission every year [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was reported that severe reductions in compressive strength and ductility may occur in GFRC with ageing [4,5], which has become a common concern for the service life of engineering members made of GFRC. e intrinsic microstructural reasons corresponding to this degradation are normally associated with chemical corrosion of fibre by the alkalinity in pore solution [6] and severe CH densification between and around fibres that results in loss of flexibility [7]. At the same time, in the global background of low carbon emission, cement industry is faced with great challenge as it contributed about 6% to total global anthropogenic CO 2 emission every year [8,9].…”
Section: Introductionmentioning
confidence: 99%